Naltrexone beyond Psychiatric Domain - Ashutosh Garg; Khyati Thapliyal; Vivek Pal Singh (Indian Journal of Medical Specialities)
Naltrexone, an opioid receptor (OR) antagonist, at its standard doses, is a United States Federal Drug Administration-approved drug for opioid and alcohol use disorders. However, with the discovery of nonneuropsychiatric effects of OR signaling with low-dose naltrexone, it has found novel applications in inflammatory, malignant, insulin sensitivity-related, and chronic pain conditions. Lower doses also ameliorate its adverse effects. Its off-label use in the abovementioned situations has proven to be cost-effective against costly immunomodulating and antineoplastic drugs. Its lower cost and miniscule margin of interest have precluded in-depth analysis by the pharmaceutical industry. So far, only animal studies, cell culture studies, and case reports have been conducted, some of which exhibit promising benefits. There is a dearth of much-needed quality trials.